Two new phenolic glycosides from the seeds of Citrullus lanatus. Issue 3 (1st February 2020) - Zhang, Xiao-Qian; Shi, Jing; Feng, Shi-Xiu; Xue, Lin; Tian, Li-Ping
Abstract: Two new phenolic glycosides, named lanatusosides C (1 ) and D (2 ), together with four known compounds (3 -6 ), were isolated from the seeds of Citrullus lanatus . Among them, compounds 3 and 4 were isolated from Cucurbitaceae for the first time, and compound 5 was reported from this plant for the first time. Their structures were elucidated by means of extensive spectral analysis, including HR-ESI-MS, 1 H and 13 C NMR techniques. The isolated new compounds were evaluated for cytotoxic activity against HepG2 cell line, of which compound 1 demonstrated weak cytotoxicity against the tested cell line. Abstract :